Case Report: Successful Treatment With Anti-C5 Monoclonal Antibody in a Japanese Adolescent Who Developed Thrombotic Microangiopathy After Autologous Bone Marrow Transplantation for Malignant Lymphoma - Shimizu, Shoichi; Morohashi, Tamaki; Kanezawa, Koji; Yagasaki, Hiroshi; Takahashi, Shori; Morioka, Ichiro (Frontiers in Pediatrics, 2022)
Background: Transplant-associated thrombotic microangiopathy (TA-TMA) is a serious complication of bone marrow transplantation (BMT). Recently, abnormalities in the complement system have been identified in the pathogenesis of TA-TMA, and there are series of reports stating that anti-C5 monoclonal antibody (eculizumab) is effective in patients with high levels of the membrane attack complex (C5b-9). Case Presentation: A 12-year-old boy underwent autologous BMT after receiving high-dose chemotherapy for malignant lymphoma. The patient was engrafted on day 19 after transplantation; however, hemolytic anemia and non-immune thrombocytopenia persisted, and haptoglobin decreased on day 46. Moreover, on day 83, the patient developed pulmonary hemorrhage, hypertension, severe proteinuria, hematuria, and acute kidney injury (AKI). Pulmonary bleeding stopped with daily platelet transfusion and hemostatic agents, but reappeared on day 100. Based on the presence of destruction of red blood cells, elevated lactate dehydrogenase levels, negative direct and indirect Coombs tests, normal ADAMTS13 levels, hemolytic anemia, non-immune thrombocytopenia, and AKI, the patient was diagnosed with systemic TA-TMA and we initiated plasma exchange (PE) and continuous hemodialysis for AKI. High C5b-9 levels were identified at the start of the series of PE, therefore we decided to administer eculizumab. After three courses of eculizumab, no pulmonary hemorrhage was observed, and anemia, thrombocytopenia, renal dysfunction, hematuria, and proteinuria all tended to improve. Three years after transplantation, the patient is alive and does not require eculizumab. Discussion: Eculizumab is a humanized monoclonal antibody that binds complement protein C5, preventing cleavage C5 and the formation of C5b-9. In this case, TA-TMA could not be controlled with PE alone. We therefore decided to use eculizumab relatively early based on the high C5b-9 level and could resolve the momentum of TA-TMA. Conclusion: In previous reports, TA-TMA typically occurred in early post-allogeneic BMT of patients with lymphoma or in post-autologous BMT of patients with neuroblastoma and was treated with eculizumab. We here reported that eculizumab could be successful treatment for TA-TMA in post-autologous BMT of patient with lymphoma.